Book Notes [32, Fall 1993] - Palmer, Bryan D.; Kealey, Gregory S. (Labour / Le Travail, 1993)
The article briefly reviews "A Differerent Kind of State? Popular Power and Democratic Administration," edited by Gregory Albo, David Langille. and Leo Panitch, "Belonging: The Meaning and Future of Canadian Citizenship," edited by William Kaplan, "Policing Canada's Century: A History of the Canadian Association of Chiefs of Police," by Greg Marquis, "Aberhart: Outpourings and Replies," edited by David R. Elliott, "The Voyages of Jacques Cartier," by Ramsay Cook, "Habitants and Merchants in Seventeenth Century Montreal," by Louise Dechtne, "New England Planters in the Maritime Provinces of Canada, 1759-1800," compiled by Judith A. Norton, "Creed and Culture: The Place of English-Speaking Carholics in Canadian Society, 1750-1930," edited by Terrence Murphy and Gerald Stortz, "While the Women Only Wept: Loyalist Refugee Women in Eastern Ontario," by Janice Potter-MacKinnon, "Cultivation and Culture: Labor and the Shaping of Slave Life in the Americas," edited by Ira Berlin and Philip D. Morgan, "Farm to Factory: Women 's Letters, 1830-1860," edited by Thomas Dublin, "Gender and American History Since 1890," edited by Barbara Melosh, "Industrial Democracy in America: The Ambiguous Legacy," edited by Nelson Lichtenstein and Howell John Harris, "Race in America: The Struggle for Equality" edited by Herbert Hill and Jamcs E. Jones, Jr., "The Land and the Loom: Peasants and Profit in Northern France, 1680-1800," by Liana Vardi, "Harold Laski: A Political Biography," by Michael Newman, "Socialist Parties and the Question of Europe in the 1950s," edited by Richard T. Griffiths, "Keeping Heads Above Water: Salvadorean Refugees in Costa Rica," by Tanya Basok, "The Althusserian Legacy," edited by E. Ann Kaplan and Michael Sprinker, "Capitalism Versus Anti-Capitalism: The Triumph of Ricardian over Marxist Political Economy," by Paul Fabra, and "Labor Demand," by Daniel S. Hamemesh / reviews by Bryan D. Palmer -- "Tramps, Workmates and Revolutionaries: Working-Class Stories of the 1920s," edited by H. Gustav Klaus / review by Gregory S. Kealey.